An autopsy report case of rape victim by the application of PSA test kit as a new innovation for sexual assault investigation in Thailand - Jate Talthip (2018)
The case of a 30 year-old Thai female found dead on the floor at the base of a small monument on Rajadumnern Road, Bangkok, Thailand with blood stains around the body and a naked bottom. The scene investigation and autopsy findings suggested a sexual assault and multiple sharp force injuries. The approach to the postmortem examination using different laboratory tests is reviewed. The specificity and sensitivity of prostate specific antigen (PSA) in specimens from rape victims is better than acid phosphatase test. The ELISA test for PSA was tested to confirm the PSA test kit. The present report suggests the PSA test kit in addition to conventional sperm smear and acid phosphatase test for sexual assault investigation in Thailand.